An Exploration of Audio and Audio-Visual Media in Teaching Arabic Listening (Istimā‘) at Madrasah Aliyah - Halimah Zuhdiyyah; Hamdi Hamdi (Gunung Djati Conference Series, 2026)
This study aims to explore the use of audio and audio-visual media in teaching Arabic listening (Istima‘) at Madrasah Aliyah. The research employs a descriptive qualitative approach to provide an in-depth portrayal of how audio and audio-visual media are utilized in Arabic listening instruction. Primary data were obtained from teachers and students through interviews, observations, and direct experiences related to media use, while secondary data were collected from lesson plans, syllabi, textbooks, and other supporting documents. Data collection techniques included interviews, observations, and documentation. Data analysis involved repeated cycles of data reduction, data display, and conclusion drawing to produce accurate and contextual findings. The results show that Arabic listening instruction at Madrasah Aliyah has employed various audio and audio-visual media, such as recorded conversations, vocabulary (mufradāt) recordings, songs, podcasts, videos, and films. These media provide authentic language input and enhance students’ comprehension and motivation. However, their use is not yet evenly implemented due to limited equipment, teachers’ varying competencies, and students’ difficulties in understanding certain accents or vocabulary. With adequate facilities and proper training, the effectiveness of these media can be significantly improved.